Understanding EAP Learners$1 (BBeliefs about Language Learning from a Socio-cultural Perspectives A Longitudinal Study at an EMI Context in Mainland China - Li, Chili; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This book focuses on the dynamic nature of EAP (English for academic purposes) learners$1 (Bbeliefs about language learning in their shift from an EFL (English as a foreign language) environment to an EMI (English as the medium of instruction) setting in mainland China. It adopts a mixed method paradigm, whose quantitative part aims to capture the general dynamic feature of the selected student population, while its qualitative part attempts to unveil the process of change in beliefs about language learning among the sample. It is hypothesized that the change in their beliefs about language learning is the result of the interplay between the learners$1 (Bagency and the mediation of the contextual realities at the institutional and social levels.s
Chapter 1. Introduction -- Chapter 2. Literature Review -- Chapter 3. Research Methodology -- Chapter 4. Results Regarding Beliefs about Language Learning -- Chapter 5. Socio-cultural Interpretation of the Results -- Chapter 6. Conclusions and Recommendations. .
Keywords: Language and languages$1 (BStudy and teaching.s; Sociolinguistics; Language Teaching and Learning; Language Education; Sociolinguistics